Prevalence and Antimicrobial Susceptibility of Bacterial Uropathogens Isolated from Pediatric Patients at Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia - Yamirot Merga Duffa; Kumera Terfa Kitila; Dereje Mamuye Gebretsadik; Adane Bitew (International Journal of Microbiology)
Background. Urinary tract infection (UTI) is considered as the most common bacterial infection seen among the pediatric patients. Objective. This study was carried out in order to determine the prevalence of urinary tract infection in pediatric patients, identify bacterial uropathogens responsible for the infection, and study the antibiotic sensitivity patterns of bacterial isolates. Materials and Methods. A cross-sectional study designed and conducted from January to April 2014. Clean-voided midstream urine specimens were obtained from 384 pediatric patients less than or equal to 15 years in sterile universal bottles. Urine collected from each patient was inoculated onto CLED and blood agar plates using a calibrated inoculating loop with a capacity of 0.001 ml. Inoculated plates were incubated for 24–48 hours at 37°C at inverted position aerobically. Bacterial isolates were indentified and characterized by Gram stain and by using an array of standard routine biochemical tests. The antimicrobial susceptibility test was carried out by using the Kirby–Bauer disc diffusion method. Frequency distribution tables were used to describe the findings. Logistical regression was also used to estimate crude odds ratio (COR) with 95% confidence interval (CI) of positive responses to the different variables, and P values less than 0.05 were taken as statistically significant. Result. In this study, a total of 384 patients (199 males and 185 females) aged less than or equal to 15 years from whom urine samples were collected were enrolled. Of these patients, 61 (15.9%) had significant bacteriuria. Of the 185 females, 36 (19.5%) came up with positive cultures, while 25 (12.6%) of the 199 males had significant bacteriuria, and the largest number of study subjects were below the age of 3 years, and the largest positive culture was obtained from this age group, accounting for 35 (57.4%.) out of 61 positive cultures. Bacterial species belonging to six genera were isolated and identified from 61 positive cultures, and the genera were Escherichia, Klebsiella, Staphylococcus, Proteus, Acinetobacter, and Enterococcus. E. coli was isolated in 28 cases (49.5 %), followed by Klebsiella spp. in 17 cases (27.9%), Staphylococcus spp. in 5 patients (8.2%.) (S. aureus in one and coagulase-negative staphylococci in 4 cases), Enterococcus in 7 cases (11.5%), Proteus spp. in 3 cases (4.9%), and Acinetobacter in one case (1.6%). Of the bacterial isolates, E. coli was found out to be the most common pathogen followed by Klebsiella spp. Furthermore, E. coli and Klebsiella spp. were the most common pathogens in female patients accounting for 71.4% and 64.7%, respectively. Regarding susceptibility tests, E. coli and Klebsiella spp. were not 100% susceptible to any of the 11 antibiotics tested. Acinetobacter spp. had 100% resistance to three antibiotics: gentamicin (GN), trimethoprim-sulfamethoxazole (SXM), and augmentin (AMP). But they were 100% susceptible to ciprofloxacin (CIP), cefuroxime (CXM), norfloxacin (NOR), and ceftazidime (CAZ). On the contrary, Proteus spp. was 100% sensitive to all drugs except to nitrofurantoin. Species of Enterococcus had resistance of 71.4% to chloramphenicol (C) and 85.7% to both SXM and erythromycin. S. aureus was 100% susceptible to almost all drugs, while coagulase-negative staphylococci were not as susceptible as S. aureus. Multidrug resistance to two or more drugs was observed in 73.7% of the bacterial isolates. Conclusion. This study determined the prevalence of urinary tract infection in pediatric patients and highlighted the major bacterial uropathogens involved in UTI for the first time in the country. Furthermore, bacterial pathogen species and their frequency was consistent with the usually reported pattern, with E. coli being the most common organism isolated in cases of urinary tract infections followed by Klebsiella spp. Most of the bacterial isolates were multidrug resistant, and it is therefore suggested that appropriate antimicrobials should be administered to reduce the risk of multidrug resistant organisms developing and avert ineffectiveness of antibiotics. This condition indicates that antibiotic selection should be based on knowledge of the local prevalence of bacterial organisms and antibiotic sensitivities rather than empirical treatment. The present study indicated that ciprofloxacin (CIP), ceftazidime (CAZ), cefotaxime (CTX), cefuroxime (CXM), clindamycin (DA), and ceftriaxone (CRO) were the best antibiotics for the treatment of Gram-negative and Gram-positive bacterial uropathogens, respectively, in the study area relatively.